Rewrite the equation by completing the square.
x^2 + 3x – 28 = 0
![Rewrite the equation by completing the square x2 3x 28 0 class=](https://us-static.z-dn.net/files/d0b/0550cee95a775b8873893e692ca09ac5.png)
this is all i got sorry if it wrong
( x − 4 ) ( x + 7 ) = 0 If any individual factor on the left side of the equation is equal to 0 , the entire expression will be equal to 0 . x − 4 = 0 x + 7 = 0
Set the first factor equal to 0 and solve. x=4 Set the next factor equal to 0 and solve. x = − 7 The final solution is all the values that make ( x − 4 ) ( x + 7 ) = 0 true. x = 4 , − 7